Analysis of Sensitive Interventions through Drinking Water Supply and Access to Sanitation in Accelerating the Reduction of Stunting in Sempung Polling Village, Lae Parira Subdistrict, Dairi Regency, 2023 - nolia, helfi; Harnat , Robert (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Poor quality of clean water and sanitation is a significant risk factor for stunting, a condition where a child's height is not appropriate for their age. Globally, 149.2 million children (22%) were stunted in 2020, with Asia contributing the highest number of cases (79 million). Southeast Asia has the second-highest prevalence (27.4%) after South Asia. According to the Asian Development Bank (ADB), Indonesia ranks second in Southeast Asia for stunting prevalence (31.8%). The Indonesian Ministry of Health reported that as of November 2018, Indonesia's sanitation coverage was 73.9%, and by 2020, 94% of drinking water facilities had been monitored. In Dairi Regency, the prevalence of stunting in 2022 was 13.53%, with 3,025 stunted children. Research Objective is to analyze risk factors related to access to water and sanitation. The study uses a cross-sectional method, with purposive sampling techniques, involving a research sample of 60 children under five. Bivariate analysis was conducted using the chi-square test with ἀ=0.05, and multivariate analysis was performed using logistic regression. Results: The variable that most significantly contributes to the incidence of stunting in Sempung Polling Village, Dairi Regency, is poor drinking water management. The positive beta (β) coefficient contribution of 3.115 with an Exp (β) of 3.627 indicates that poor drinking water management at the household level increases the risk of stunting in toddlers by 3.7 times.